Outsourcing the brains: The epistemic power of consultancies in criminal justice - Franko, Katja (Theoretical criminology, 2025)
The consulting industry enjoys an increasingly close relationship with the state, including criminal justice institutions. However, this development, previously described as ‘consultocracy’, is empirically unexamined within criminal justice scholarship. Drawing on document analysis of calls for tenders and interviews with consultants working within the criminal justice field in Norway, the article examines what kind of knowledge and expertise is provided by consultants, and how they obtain and exercise their epistemic power. In an increasingly cost-conscious public sector, which is acutely aware of the urgency of digital transformations, the consultancy industry exerts a growing influence on the organizational infrastructure of criminal justice, its evidence base and modes of knowledge production. Consultants are active agents in the proliferation of ideas that are re-shaping how criminal justice agencies understand the social problems they deal with, and the responses to them, as well their role and function in society.